Ultrasonic Studies in Binary Mixtures of N-Propyl Formate with 1-Alcohols At 303 K - Elangovan, S.; Mullainathan, S. (Asian Journal of Chemistry, 2015)
Density (r), viscosity (h) and ultrasonic velocity (U) have been measured for binary mixtures composed of n-propyl formate with 1-butanol, 1-pentanol and 1-hexanol at 303 K. From the experimental data, various parameters such as adiabatic compressibility (b), free length (Lf), free volume (Vf), Internal pressure (pi), viscous relaxation time (t) and Gibbs free energy (DG) have been deduced. Excess values of the above parameters (bE, LfE, VfE, piE, tE and DGE) from their ideal values have also been calculated and fitted in Redlich-Kister polynomial equation. The results have been interpreted in terms of molecular interactions. The deviations in sign and excess values from the ideal mixing reveal that strength of intermolecular interactions between n-propyl formate with selected 1-butanol, 1-pentanol and 1-hexanol have been observed in the order of 1-butanol < 1-pentanol < 1-hexanol.